2018
DOI: 10.4088/pcc.18m02299
|View full text |Cite
|
Sign up to set email alerts
|

Acute Blood Pressure Changes Associated With Antipsychotic Administration to Psychiatric Inpatients

Abstract: Initiation of certain antipsychotic medications may be associated with statistically significant acute BP changes. These findings require further evaluation in well-designed prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…The female patients seemed to have more stable readings of blood pressure, despite the long-term use of SGAs. Parks et al reported an acute decrease in blood pressure in patients three days post-initiation of SGA [42]. Moreover, mean systolic blood pressures were found to have had slightly decreased after 12 months of SGA use [43].…”
Section: Discussionmentioning
confidence: 99%
“…The female patients seemed to have more stable readings of blood pressure, despite the long-term use of SGAs. Parks et al reported an acute decrease in blood pressure in patients three days post-initiation of SGA [42]. Moreover, mean systolic blood pressures were found to have had slightly decreased after 12 months of SGA use [43].…”
Section: Discussionmentioning
confidence: 99%
“…In patients diagnosed with schizophrenia, short-term treatment (3 days) with clozapine induced transient hypotension (Parks et al, 2018), most likely due to direct α1 adrenergic receptor antagonism. During 8 weeks of clozapine treatment, heart rate increased and blood pressure shifted toward hypertension (Norman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of antipsychotic medications on blood pressure is not clear. A retrospective study found that olanzapine and risperidone raised blood pressure during the first three days after initiation, but clozapine reduced blood pressure (18). Prospective studies are required for further evaluation of this, but even if there is not a direct effect on blood pressure, medication-induced weight gain will contribute to an increased risk of hypertension.…”
Section: Contribution Of Antipsychotic Medications To Metabolic Syndrome Componentsmentioning
confidence: 99%